Job satisfaction of university teachers: A systematic literature review (2010-2021) - Yang, Qi; Hoque, Kazi (Journal of University Teaching and Learning Practice, 2023)
In this study, the authors searched, read, collated and reflected on the past research on the factors affecting university teachers' job satisfaction for the period of 2010-2021. In this systematic literature review, we can understand that the factors that influence the job satisfaction of university teachers are broadly divided into three areas, including the university, the teachers themselves, and the students. The authors have therefore systematically summarized and analyzed a total of ten areas of influence on schools, six variables under teachers' own factors, and two factors under students. Through this literature review, we found that there is still a lack of research on various aspects, and because of this, we hope that through this systematic analysis, we can extend and break through the factors of teachers' job satisfaction in the future, and provide constructive guidelines for the subsequent development of school policies, teacher support work and student evaluation, in order to better and comprehensively improve teachers' job satisfaction, so as to better achieve teaching goals and improve teaching quality.